Agroforestry to Support Trees and Protect Against Air Pollution: A Review - Adiputra, Gede Ketut (KnE Life Sciences, 2022)
The high rate of land conversion may jeopardize natural resources vital to Balinese culture, as well as the forest’s ability to maintain a healthy environment. Agroforestry is thought to have a significant environmental benefit in terms of reducing air pollution and respiratory diseases. This research aimed to find a solution to reduce air pollution that is harmful to people’s health. Relevant articles were found by searching through databases such as Google Scholar, Research Gate, Wiley Online Library, and others. According to the findings, respiratory diseases have been increasing and these have been linked to rising air pollution, implying that air pollution facilitates viral infections. Forest cover should be increased to help reduce air pollution caused by fossil fuel combustion from road traffic. It is proposed that increasing the production of tolerant crops in mixed culture with trees can help to maintain tree cover. Agroforestry is becoming an important complement to the native forest in terms of protecting people from air pollution and respiratory disease. Keywords: agroforestry, tree protection against air pollution, land conversion, deforestation